A study of one soil, its relatives and contaminants by arbitrary primed PCR with 50mer based analysis. (December 2015) - Burgoyne, Leigh; Koh, Lin; Catcheside, David
Abstract: Next generation sequencing provides the means of comparison of metagenomes which can be used for forensic purposes. Here, we describe an economic approach that deals with the problems of expense of data generation and dealing with and analysing large data sets.